A new method for detecting proanthocyanidin content in wheat reveals the relationship between R‐1 gene to grain color deepness. Issue 2 (7th December 2022) - Himi, Eiko; Matsuura, Takakazu; Miura, Hideho; Yoshihara, Naoya; Maekawa, Masahiko
Abstract: Background and Objectives: Grain color of wheat is one of the important quality parameters that affect the flour color and its product such as bread and noodles. R‐1 gene, a regulator of grain color, is located on chromosomes 3A, 3B, and 3D, and at least one dominant allele is responsible for the red color of the grain. It has been thought that the number of dominant R‐1 allele relates to the deepness of the red color of grain; however, methods to quantify grain pigments have not been established yet. The aim of this work was to establish a method for quantifying pigments using 4‐dimethylaminocinnamaldehyde (DMACA), which reacts with precursors of which constitute major pigments of wheat grain. Findings: Wheat proanthocyanidins were detectable in immature seeds by the DMACA method but became undetectable as the grains matured. Comparison between lines with the same flowering time and genetic background revealed that the amount of pigment was determined by the number of dominant R‐1 alleles. Conclusions: We established the DMACA method for quantifying wheat seed pigments and used that to clarify the relationship between the number of R‐1 alleles and pigment content. Significance and Novelty: Since the method developed in this study is not affected by other pigments such as chlorophyll, it can be universally applied to other plants and tissues in addition to wheat grains.